Experimental Analysis of rGO-V₂O₅ Nanocomposites for Sustainable Water Remediation Completed with Bibliometric Analysis Toward Achieving Sustainable Development Goals (SDGs) - Thamer Adnan Abdullah; Haneen Lateef Khaleel; Ammar W. Saeed; M. N. Mohammed; Qusay Al-Obaidi; Mukhtar Ali Hussein; Wassef Abbood Mhmood; Rashed T. Rasheed; Oday I. Abdullah (Bumi Publikasi Nusantara, 2026)
This work integrates bibliometric analysis with laboratory experiments to develop nanotechnology-based water treatment technologies, aligning with Sustainable Development Goals (SDGs) on providing clean water and sanitation. A high-adsorption nanomaterial composed of reduced graphene oxide (rGO) doped with vanadium pentoxide (V₂O₅) was prepared using thermal doping and analyzed using XRD, FESEM, and FTIR techniques. This composite demonstrated the ability to remove 68.98% of methyl orange dye in just 30 minutes. Kinetic and adsorption studies showed conformed to a quasi-second-order kinetic model and a Langmuir single-layer adsorption model, indicating strong chemisorption and surface homogeneity. This high performance is attributed to the synergistic effect between V₂O₅ and rGO in contributing high surface area, improving electron transport, and enhancing effective sites for capturing dye molecules. This nanocomposite is a sustainable and economical option for supporting the smart architecture of urban water systems, contributing to SDGs.